Problems of the Realization of Admistrative-Jurisdictional Powers of Local Authorities in the Field of Public Order Protection and Crime Prevention - Aleksandr G. Avdeiko; Anatolii M. Kononov (Сибирское юридическое обозрение, 2017)
The article discusses the existing forms of realization of administrative-jurisdictional powers in the field of public order protection and crime prevention. The problems of organization of activity are analyzed of commissions on juvenile affairs and protection of their rights, the administrative commissions established in municipalities. The necessity of the creation of municipal militia as a solution to the issue of the realization of local self-government bodies of administrative-jurisdictional powers.